Pengaruh Efektivitas Pengendalian Internal dan Kesesuaian Kompensasi terhadap Kecenderungan Kecurangan Akuntansi dengan Audit Internal sebagai Variabel Pemoderasi di LPD Se-Kabupaten Karangasem - I Kadek Agus Aditya Kusuma; Ni Luh Putu Mita Miati; A.A. Putu Mirah Purnama Sari; I Gde Agung Wira Pertama (Universitas Pendidikan Ganesha, 2022)
Of the number of LPDs in Bali, there are still LPDs with unhealthy information, even prohibited based on this the object of this study is the influence of the effectiveness of internal control and the suitability of compensation to the tendency of accounting fraud with internal audits as a moderating variable. Research is done by empirical studies. This study was conducted at the Village Credit Institute (LPD) sampling technique through the slovin formula, amounting to 65 samples and data collection with questionnaires. Data analysis techniques use the partial last square model with the help of smart PLS 3.0 applications. The test results explained that the effectiveness of internal control and compensation suitability had a negative effect on the tendency of accounting fraud while internal audits were not able to moderate the influence of the effectiveness of internal control and the suitability of compensation to the tendency of accounting fraud.